How computers work. - White, Ron, ....- (Indianapolis : Que, 2004)
Samenvatting:How Computers Work, 7th Edition has been one of the best-selling computerbooks for the last 10 years. This four-color visual book is a must-havefor any computer user, from novice to expert. The rich graphics andintricate details about the inner workings of computers have been admiredfor years by consumers, instructors, professionals, and readers of allages. To celebrate this milestone, this edition is the 10th AnniversaryEdition and it has a new lower price of $29.99. The 10th AnniversaryEdition has been completely updated with new coverage of: Wi-Fi, Viruses,Security, Photo Printers, Centrio notebooks, and many updates to existingtechnologies. A fresh cover and interior provide the reader with superiorusability and it is the most aesthetically-pleasing edition yet!
Keywords: Computers